A role for Phospholipase D in Drosophila embryonic cellularization. - LaLonde, M.; Janssens, H.; Yun, S.; Crosby, J.; Redina, O.; Olive, V.; Altshuller, Y.M.; Choi, SY.; Du, G.; Gergen, J.P.; Frohman, M.A. (BMC Developmental Biology, 2006)
Cellularization of the Drosophila embryo is an unusually synchronous form of cytokinesis in which polarized membrane extension proceeds in part through incorporation of new membrane via fusion of apically-translocated Golgi-derived vesicles.We describe here involvement of the signaling enzyme Phospholipase D (Pld) in regulation of this developmental step. Functional analysis using gene targeting revealed that cellularization is hindered by the loss of Pld, resulting frequently in early embryonic developmental arrest. Mechanistically, chronic Pld deficiency causes abnormal Golgi structure and secretory vesicle trafficking.Our results suggest that Pld functions to promote trafficking of Golgi-derived fusion-competent vesicles during cellularization.